Rebasing a Half Hollow Maxillary Complete Denture to Rectify Processing Error – A Case Report - Pathak, Bibha; Parajuli, Prakash Kumar (Journal of BP Koirala Institute of Health Sciences, 2025)
Presence of surface or subsurface voids in a denture that has been processed are often encountered due to errors during laboratory processing of dentures. Errors during proportioning of monomer and polymer, improper mixing technique, inadequate pressure and material during packing and monomer vaporization during curing cycle can result in porosities which are undesirable. Rebasing can provide a great economic option in some cases of newly processed porous denture base, thereby avoiding the long and several appointments required for the construction of a new denture. This clinical report describes a rebasing technique using flask method to correct extensive porosities in newly processed half hollow maxillary complete denture.